Sur la frontière, quelles représentations des enfants ? Enquête dans le Nord de la France - Xavier Leroux; Maud Verherve (EchoGéo)
What king of geographical sense does a child make of a cross-border region? The article attempts to show and understand how the border is depicted in their mind, while school has to teach them what it is. Our survey, carried out in primary school classes in the cross-border region of North of France, collected these representations and attempts to show that drawing is a relevant methodological tool.